2022
DOI: 10.20535/2411-1031.2022.10.2.270403
|View full text |Cite
|
Sign up to set email alerts
|

Method of calculation of protection of information from the average length of the road between users in social networks

Abstract: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The most closely related works are [1,2,5,8,9], which analyze the impact of parameters such as the size of social media development, user interactions and relationships, network clustering, the spread and volume of information, and their actions on ISI. In [2] analyzed the impact of the duration of the path between clients and other components of the characteristics of social media on the information security indicator. It was shown that the model is nonlinear.…”
Section: Concept and Objectives Of Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…The most closely related works are [1,2,5,8,9], which analyze the impact of parameters such as the size of social media development, user interactions and relationships, network clustering, the spread and volume of information, and their actions on ISI. In [2] analyzed the impact of the duration of the path between clients and other components of the characteristics of social media on the information security indicator. It was shown that the model is nonlinear.…”
Section: Concept and Objectives Of Analysismentioning
confidence: 99%
“…The graphical dependence of the differential [2] of the UDPC (Fig. 1), the differential of the ISI (Fig.…”
Section: Features Isi In Sm Considering Characteristics Udpcmentioning
confidence: 99%
See 2 more Smart Citations